1999
DOI: 10.1046/j.1365-8711.1999.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

A measurement of the transverse velocity of Q2237+0305

Abstract: Determination of microlensing parameters in the gravitationally lensed quasar Q2237+0305 from the statistics of high magnification events will require monitoring for more than 100 years (Wambsganss, Paczynski & Schneider 1990). However we show that the effective transverse velocity of the lensing galaxy can be determined on a more realistic time-scale through consideration of the distribution of light-curve derivatives. The 10 years of existing monitoring data for Q2237+0305 are analysed. These data display st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 24 publications
4
45
0
2
Order By: Relevance
“…In spite of the fact that the range of typical determinations of dM/dt is not excessively broad, all the individual 1σ measurements are in agreement with no accretion, but a flow of matter of almost 1000ε M yr −1 cannot be ruled out. On the other hand, one direct constraint on v d was recently reported by Wyithe et al (1999). This group is involved in a project to interpret the QSO 2237+0305 microlensing light-curves, and as a part of the program, they derived an upper limit of v t < 500 km s −1 , where v t is the galactic transverse velocity (Ω 0 = 1, λ 0 = 0).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In spite of the fact that the range of typical determinations of dM/dt is not excessively broad, all the individual 1σ measurements are in agreement with no accretion, but a flow of matter of almost 1000ε M yr −1 cannot be ruled out. On the other hand, one direct constraint on v d was recently reported by Wyithe et al (1999). This group is involved in a project to interpret the QSO 2237+0305 microlensing light-curves, and as a part of the program, they derived an upper limit of v t < 500 km s −1 , where v t is the galactic transverse velocity (Ω 0 = 1, λ 0 = 0).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The value of this "effectiveness parameter" is a ≈ 1.3 (see Wambsganss & Kundic 1993;Kundić & Wambsganss 1995, for details). Since the central velocity dispersion of the lensing galaxy in Q2237+0305 has been measured: v µlens 215 km s −1 (Foltz et al 1992), we can use that and infer an even lower value for the upper limit on the effective velocity of the bulk motion (the velocity dispersion at the location of the images could be slightly different, though): Wyithe et al (1999) presented the first determination of the effective transverse velocity of the lens galaxy in Q2237 via microlensing. Here we compare this approach to ours.…”
Section: CLmentioning
confidence: 99%
“…Q2237+0305 is the best studied quasar microlensing system. With ten years of monitoring data, Wyithe et al (1999) used the derivatives of the observed microlensing lightcurves to put limits on the lens galaxy tranverse velocity of Q2237+0305. Very recently, Kochanek (2004) developed a method for analysing microlensing lightcurves based on a χ 2 statistics which includes the transverse velocity of the source as an output parameter.…”
Section: Introductionmentioning
confidence: 99%
“…This makes possible some estimations of certain GLS characteristics, in particular, the source size [25]. For example, in case of the well-known GLS Q2237+0305 (Einstein Cross), several HAEs was observed [26][27][28] and the estimates of the source size have been obtained within different source models [16,[29][30][31][32][33][34].…”
Section: Preliminary Commentsmentioning
confidence: 99%